Guidelines for Using Discretionary Powers No Contrary to the Law - Jeyalee, Ongard; Thanyphaisan, Sirirak (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
State officials must exercise state power based primarily on the provisions of rules or laws. This is because state institutions are legally established and granted authority by law. Therefore, the exercise of state power by officials must be lawful in every action, in accordance with the principles of the rule of law. However, the exercise of state power known as discretionary power, though governed by legal frameworks to prevent bias or misuse, still often leads to disputes. Many cases arise from the unlawful use of discretionary power by state officials. This clearly demonstrates that the existing laws are insufficient to fully safeguard against the misuse of administrative discretion. Therefore, there should be clearly written guidelines for the use of discretionary power by administrative bodies, to prevent any misuse, as stipulated in the Act on Establishment of Administrative Courts and Administrative Court Procedure, Section 9, paragraph one (1).